2019
DOI: 10.1002/ejic.201900108
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometalated Ruthenium(II) NHC Complexes with Imidazo[1,5‐a]pyridine‐Based (C^C*) Ligands – Synthesis and Characterization

Abstract: We present the synthesis and characterization of cyclometalated ruthenium(II) NHC complexes with phenylsubstituted imidazo[1,5-a]pyridine C^C* ligands. The corresponding p-cymene complexes can be reacted with bipyridine to form bisheteroleptic ruthenium(II) dyes. The compounds [a] 1956 have been characterized by one-and two-dimensional 1 H/ 13 C NMR spectroscopy, elemental analysis, cyclic voltammetry, infrared spectroscopy, as well as solid-state structure (X-ray) analysis. 1957[a] Two independent molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Notwithstanding the widespread interest in this class of compounds, we found that the synthetic aspects leading to their preparation are still amenable to being improved. The synthetic procedures leading to Ru­(II) polypyridyl complexes bearing three equal or different diimine chelating ligands (L) were thoroughly reviewed by Spiccia and co-workers in 2004 .…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the widespread interest in this class of compounds, we found that the synthetic aspects leading to their preparation are still amenable to being improved. The synthetic procedures leading to Ru­(II) polypyridyl complexes bearing three equal or different diimine chelating ligands (L) were thoroughly reviewed by Spiccia and co-workers in 2004 .…”
Section: Introductionmentioning
confidence: 99%
“…They allow the formation of C^C* cyclometalated complexes with Ir(III), 36 Pt(II), 37 and Ru-(II). 38 We prepared the chloride salts of the pro-ligands (H 2 L tBu ) + and (H 2 L OMe ) + which associate a fused imidazo [1,5a] pyridinium ring and an electron-rich 2,4-(di-tert-butyl)phenol or 2-(tert-butyl)-4-methoxyphenol, respectively (Scheme 1). The Ni(II) complexes of H 2 L tBu and H 2 L OMe were isolated (Scheme 2), and their electrochemical behavior was investigated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Imidazo [1,5- a ] pyridinium ligands bearing N -aryl substituents are an example of unusual NHC structures derived from imidazoliums. They allow the formation of C^C* cyclometalated complexes with Ir­(III), Pt­(II), and Ru­(II) . We prepared the chloride salts of the pro-ligands (H 2 L tBu ) + and (H 2 L OMe ) + which associate a fused imidazo [1,5- a ] pyridinium ring and an electron-rich 2,4-(di- tert -butyl)­phenol or 2-( tert -butyl)-4-methoxyphenol, respectively (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23] Replacement of one or several pyridine ligand sites by Nheterocyclic carbenes (NHCs) has received surprisingly little attention. [24][25][26][27] To gain an insight into the photochemical reactions of carbene complexes, it is necessary to characterize the lowest-lying electronic excited states and their photophysical deactivation mechanisms. After the first successful isolation of N-heterocyclic carbene (NHC) by Arduengo et al [28] in 1991, there has been an immense growth in the field of chemical, [14,[29][30][31] structural, [32][33][34][35] biomedical [36][37][38][39] and photophysical properties.…”
Section: Introductionmentioning
confidence: 99%